Diagnosis of malignancies in children with musculoskeletal complaints - Gonçalves, Marcela; Terreri, Maria Teresa Ramos Ascensão; Barbosa, Cássia Maria Passarelli Lupolli; Len, Cláudio Arnaldo; Lee, Lucia; Hilário, Maria Odete Esteves (São Paulo Medical Journal, 2005)
CONTEXT: Musculoskeletal complaints may be as- sociated with neoplasias as an initial manifestation of the disease. When these symptoms predominate at the onset of the disease, the differential diagnosis includes several rheumatic diseases. OBJECTIVE: To assess the frequency, clinical features and types of cancer manifested in chil- dren presenting with musculoskeletal complaints over a seven-year period. TYPE OF STUDY: Retrospective. SETTING: Discipline of Allergy, Clinical Immu- nology and Rheumatology, Universidade Federal de São Paulo — Escola Paulista de Medicina. METHODS: The medical records of patients with musculoskeletal complaints and ﬁnal diagnosis of malignant disease were reviewed. The data collected were: age when symptoms initially presented, age at diagnosis, clinical features presented, labora- tory ﬁndings, and the initial and ﬁnal diagnoses. RESULTS: A ﬁnal diagnosis of cancer was found in nine out of 3,528 patients (0.25%) whose ini- tial symptom was musculoskeletal pain. The mean time between disease onset and ﬁnal diagnosis was ﬁve months. The most common features pre- sented were pauciarticular arthritis or arthralgia involving the large joints. Juvenile rheumatoid arthritis was the most frequent initial diagnosis, in four out of nine patients. Anemia was the most frequent initial hematological change. Six out of eight patients had an increased erythrocyte sedimentation rate. The lactate dehydrogenase level was raised in ﬁve out of eight patients. The malignancies found included acute lymphocytic leukemia, acute myeloid leukemia, lymphoma, neuroblastoma and Ewing’s sarcoma. DISCUSSION: The frequency of neoplasia in patients with musculoskeletal pain resembled reports in the literature. Consumptive symptoms were not the warning signal in most of our pa- tients. In subsidiary tests, progressive anemia was the most common ﬁnding, although the peripheral blood cell count may continue to be normal for weeks or months after symptom onset. CONCLUSION: Malignancy always needs to be ruled out in cases of children with muscu- loskeletal complaints. Uncharacteristic clinical manifestations and nonspeciﬁc laboratory tests may cause difﬁculty in the ﬁnal diagnosis, and rigorous investigation should be performed.